A Multiplex Genome Editing Method for Escherichia coli Based on CRISPR-Cas12a - Ao, Xiang; Yao, Yi; Li, Tian; Yang, Ting-Ting; Dong, Xu; Zheng, Ze-Tong; Chen, Guo-Qiang; Wu, Qiong; Guo, Yingying (Frontiers in Microbiology, 2018)
Nowadays, there are variable methods for editing specific sites in the E.coli chromosome. It is feasible, in a short period of time, either to perform gene-size (~1kb) integration into a single site or to introduce deletions, short insertions or point mutations into multiple sites. However, a method for rapidly integrating multiple gene-size sequences into different sites is not developed yet. Here, we describe a method and plasmid system to simultaneously insert genes into multiple specific loci of the E. coli genome without the need for chromosomal markers. The method uses a CRISPR-Cas12a system to eliminate unmodified cells by double stranded DNA cleavage and phage-derived recombinases, λ-Red, to facilitate recombination between the chromosome and donor DNA. We achieved the insertion of up to 3 heterologous genes in one round of recombination and selection. To demonstrate the practical application of this gene-insertion method, we constructed a high-yield recombinant E.coli producing an industrially useful chemical, 5-aminolevulinic acid (ALA). Moreover, a similar two-plasmid system was built to edit the genome of extremophile Halomonas bluephagenesis.